Aurora kinases: Generators of spatial control during mitosis - Ali, Aamir; Stukenberg, P. Todd (Frontiers in Cell and Developmental Biology, 2023)
Cell division events require regulatory systems to ensure that events happen in a distinct order. The classic view of temporal control of the cell cycle posits that cells order events by linking them to changes in Cyclin Dependent Kinase (CDK) activities. However, a new paradigm is emerging from studies of anaphase where chromatids separate at the central metaphase plate and then move to opposite poles of the cell. These studies suggest that distinct events are ordered depending upon the location of each chromosome along its journey from the central metaphase plate to the elongated spindle poles. This system is dependent upon a gradient of Aurora B kinase activity that emerges during anaphase and acts as a spatial beacon to control numerous anaphase/telophase events and cytokinesis. Recent studies also suggest that Aurora A kinase activity specifies proximity of chromosomes or proteins to spindle poles during prometaphase. Together these studies argue that a key role for Aurora kinases is to provide spatial information that controls events depending upon the location of chromosomes or proteins along the mitotic spindle.